Effect of Particulate Organic Carbon Deposition on Nitrate Reduction in the Hyporheic Zone - Xue Ping; Yang Xian; Menggui Jin (Water Resources Research, 2023)
Abstract The hyporheic zone (HZ), where surface water and groundwater interact in sediments beneath streams, presents unique conditions for nutrient dynamics, such as carbon and nitrogen (N) cycling. Organic carbon (OC) in aquatic systems has two distinct forms: dissolved organic carbon and particulate organic carbon (POC). OC affects N reduction and controls the occurrence of denitrification, a primary process by which nitrate (NO3−) is removed as gas (N2 or N2O) to the atmosphere. When POC is the predominant form of OC in streams, how POC influences NO3− reduction within a HZ remains unclear. We established a new reactive transport model incorporating POC transport and filtration processes to assess how POC deposition affects NO3− removal. Sediment permeability decreases as POC is filtrated in the streambed. Nitrate influx is reduced due to POC‐induced sediment clogging. The deposited POC in the shallow streambed serves as an OC source and supports higher biogeochemical reaction kinetics because OC is an important substrate promoting microbial activities. The filtrated POC pool enhances denitrification, thus causing a higher NO3− removal efficiency. In contrast, the POC pool is typically assumed to be distributed homogeneously in sediments, potentially causing a significant underestimation of stream‐borne NO3− removal. A lower hydraulic conductivity, a smaller POC grain size, and a larger POC filtration efficiency and in‐stream POC concentration allow for extensive POC deposition within the shallow streambed that favors nitrate removal. This study provides a better understanding of N processing and an accurate estimation of NO3− removal potential in HZs.